Pegada de carbono e hídrica do cultivo de coco em sistemas de produção convencional no nordeste brasileiro - Sampaio, Ana Paula Coelho (2019)
Coconut production in the Northeast region was 74% of the national production in 2017, according to the Brazilian Institute of Geography and Statistics. Therefore, this is an evaluated and comparative work such as carbon footprints and green coconut water in the states of Alagoas, Bahia, Ceará and Sergipe. Footprints were calculated based on ISO 14067 (carbon footprint), ISO 14046 (water footprint) and following the steps of a life cycle assessment study, according to ISO 14040 and 14044 standards. The data collected refer to an orchard of dwarf coconut trees cultivated for 17 years and was adopted as functional unit 1m 3 of coconut water in natura produced in a medium year. The categories of impacts considered in the footprint studies and their assessment methods were: i) for the carbon footprint the impacts on climate change (IPCC) were evaluated; ii) for water footprint, water scarcity (AWARE), human toxicity, cancer, non-cancer and ecotoxicity in freshwater (USEtox), marine and fresh water eutrophication (ReCiPe midpoint) were evaluated. It was observed that the farm of Alagoas obtained the smallest carbon and water footprint. The Ceará farm presented the worst carbon and water footprint in relation to the other farms evaluated, due to the lower amount of water used in irrigation and lower production of coconut water per hectare. Finally, this work pointed out the need to seek improvements for the coconut production system in the Northeast. Considering the results of the identification of the critical processes and the analysis of scenarios, both for the carbon footprint and hydric, it is suggested that the fertilization be carried out efficiently, according to the recommended and the need of the crop; in addition to the possible extension of the cultivation period to 30 years, with the objective of reducing the impacts of environmental footprints and guaranteeing the productivity and sustainability of the coconut crop.